GUILTY FEELING AND REDEMPTION IN THE NOVEL AND FILM THE KITE RUNNER - Triana Dewi (Edulitics (Education, Literature, and Linguistics) Journal, 2016)
The basic difference between novel and film is that each has its own medium. The medium of film is pictures and music but the medium of novel is language. Although it is a different media buttransformation from novel to film is one of the common literary works nowadays. The best sellernovel or a famous novel usually will be adapted into a film. This research aims to describe andcompare the novel and film The Kite Runner. The analysis only focuses on the guilty feeling and theredemption described in the novel, the guilty feeling and redemption portrayed in the film and how thenovel is adapted into the film. The research is descriptive and qualitative research. The researchobjects are character of Amir, Baba and Sanaubar. In this research, the use of intertextuality ofRiffaterre theory is supported by the theory of psychological in the concept of feeling guilty andredemption. The concepts are used to describe how the guilty feeling is. The result of the research areformulated as follows 1). In the novel, Amir is actually has the guilty feeling and redemption to Babaand Hassan, Baba has guilty feeling and redemption to Amir, Hassan and Ali, and Sanaubar has theguilty feeling and redemption to Hassan. 2). In the film, the characters who have the guilty feelingand redemption are only Amir and Baba, because Sanaubar is not portrayed at all. 3)Since thisresearch is only described about the dialogue of the film, so it can conclude that the novel is welladapted into the film. The novel and the film have the same theme and same idea. So there is noconversion from novel as the hipogram to the film as the transformation. About The expansion ishappened from novel to the film because there is no character as Sanaubar (Hassan’s mother) portrayed in the film. Keywords: guilty feeling, redemption, film, adaptation, intertextuality